PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM PEMBUATAN AKTA RUPS YANG DILAKSANAKAN MELALUI MEDIA TELEKONFERENSI - Widyaswari, Ni Made Dyah Nanda (VYAVAHARA DUTA, 2020)
Cyber Notary is a concept by using the development of existing technological sophistication, by using the power of notary technology can carry out its duties and authority. With a teleconference if violations occur at the General Meeting ofShareholders (GMS), such as violations, legalization of electronic deeds, digitizing documents, and other similar matters. That way the existence of Cyber Notary requires that notaries not only be clever in the field of notary but also can master the technology in the application of Cyber Notary. Facilitating the occurrence of long distance transactions between the parties is the concept of Cyber Notary was born. Thus, the background as above is discussed regarding, Using Teleconference for General Meeting of Shareholders. What legal protection measures will be used for the parties who are holding a general meeting of shareholders with the teleconference media.This study uses normative law and several approaches, namely the legislative approach and the case approach. This study uses the analysis of legal materials using the techniques of description, evaluation and argumentation. This study found results, namely: 1. The implementation of the General Meeting of Shareholders with Cyber Notary in Law No. 40 of 2007 which describes the Limited Liability Company in carrying out a GMS by teleconfession.In the implementation of the GMS conducted by Cyber Notary in Law No. 40 of 2007 concerning Limited Liability Companies does not explicitly explain the substance of the GMS that can be carried out by teleconference. The making of aGMS deed carried out by teleconference by a Notary Public is valid as long as it meets the requirements of the GMS implementation. 2. The GMS consists of various parties including the Company Organs and Notaries. Legal protection for notaries is regulated in the provisions of article 66 of Law No. 2 of 2014 concerning the position of notary public (UUJN). Meanwhile, legal protection for the company's organs in connection with the making of the GMS Deed carried out by teleconference if a dispute arises in the future includes two matters, namely through a civil suit and Reporting or giving a complaint to the notary area supervisory assembly.